Distinctive expression patterns of glycoprotein non‐metastatic B and folliculin in renal tumors in patients with Birt–Hogg–Dubé syndrome. Issue 3 (17th February 2015) - Furuya, Mitsuko; Hong, Seung‐Beom; Tanaka, Reiko; Kuroda, Naoto; Nagashima, Yoji; Nagahama, Kiyotaka; Suyama, Takahito; Yao, Masahiro; Nakatani, Yukio
Abstract : Birt–Hogg–Dubé syndrome (BHD) is an inherited disorder associated with a germline mutation of the folliculin gene ( FLCN ). The affected families have a high risk for developing multiple renal cell carcinomas (RCC). Diagnostic markers that distinguish between FLCN ‐related RCC and sporadic RCC have not been investigated, and many patients with undiagnosed BHD fail to receive proper medical care. We investigated the histopathology of 27 RCCs obtained from 18 BHD patients who were diagnosed by genetic testing. Possible somatic mutations of RCC lesions were investigated by DNA sequencing. Western blotting and immunohistochemical staining were used to compare the expression levels of FLCN and glycoprotein non‐metastatic B (GPNMB) between FLCN ‐related RCCs and sporadic renal tumors ( n  = 62). The expression of GPNMB was also evaluated by quantitative RT‐PCR. Histopathological analysis revealed that the most frequent histological type was chromophobe RCC ( n  = 12), followed by hybrid oncocytic/chromophobe tumor ( n  = 6). Somatic mutation analysis revealed small intragenic mutations in six cases and loss of heterozygosity in two cases. Western blot and immunostaining analyses revealed that FLCN ‐related RCCs showed overexpression of GPNMB and underexpression of FLCN, whereas sporadic tumors showed inverted patterns. GPNMB mRNA in FLCN ‐related RCCs was 23‐fold more abundant than in sporadic tumors. The distinctive expression patterns of GPNMB and FLCN might identify patients with RCCs who need further work‐up for BHD. Abstract : We investigated pathological features and the expression of FLCN and glycoprotein nonmetastatic B (GPNMB) in renal tumors of BHD patients. We showed that renal tumors with FLCN germline mutations overexpress GPNMB and that they lose the intact form of FLCN.